2004
DOI: 10.1159/000080472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin A against Methotrexate-Induced Damage to the Small Intestine in Rats

Abstract: Objective: The aim of the present study was to examine whether or not the administration of vitamin A (VA) protects against methotrexate (MTX)-induced damage to small intestinal epithelium. Materials and Methods: Sixty-three male Wistar albino rats, 10–12 weeks old, weighing 240–280 g, were divided into three groups: (1) controls, (2) rats receiving MTX treatment alone, and (3) rats receiving MTX plus VA treatment. A single dose of MTX (20 mg/kg MTX in 20 ml vehicle) was administered to the rats intraperitonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Growth factors such as insulin-like growth factor 1 and keratinocyte growth factor were reported to protect mice from gastrointestinal injury by stimulating growth of the damaged intestine [10], [11]. Other studies using vitamin A [6], [12], aged garlic extract (AGE) [8], apricot, beta-carotene [13], melatonin [14] and prostaglandins [15], showed protective effect on the MTX-induced damages to the small intestine in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Growth factors such as insulin-like growth factor 1 and keratinocyte growth factor were reported to protect mice from gastrointestinal injury by stimulating growth of the damaged intestine [10], [11]. Other studies using vitamin A [6], [12], aged garlic extract (AGE) [8], apricot, beta-carotene [13], melatonin [14] and prostaglandins [15], showed protective effect on the MTX-induced damages to the small intestine in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal damage induced by the administration of antitumor drugs such as MTX is attributed to damage to the crypt cells (Taminiau et al, 1980;Yüncü et al, 2004). The present study suggests that the damage induced by MTX in the small intestine is reduced by AGE.…”
Section: Resultsmentioning
confidence: 48%
“…There are several published reports showing the use of MTX together with lecovorin, vitamin A, vitamin E, soy flour and garlic extracts. Application of vitamin A, for example, has been demonstrated to protect the small intestines from damage (Tsurui et al, 1990;Yüncü et al, 2004). Kosakai et al (1991) suggested that vitamin A may influence the crypt cells by activating protein synthesis.…”
mentioning
confidence: 99%
“…36 A similar result was proven by Yüncü et al in an experimental study performed with the supplementation of vitamin A which had antioxidant properties. 37 In our animal model, the attenuating of villi damaged was noteworthy in the intestinal mucosa after the use of GE. Furthermore, increased crypt proliferation was noticeable in our study.…”
mentioning
confidence: 63%